2013
DOI: 10.1186/1472-6963-13-16
|View full text |Cite
|
Sign up to set email alerts
|

Is 50 cent the price of the optimal copayment? - a qualitative study of patient opinions and attitudes in response to a 50 cent charge on prescription drugs in a publicly funded health system in Ireland

Abstract: BackgroundA 50 cent prescription levy was introduced in 2010 on the General Medical Services (GMS) scheme (Irish public health insurance). This study sought to examine patient attitudes and opinions surrounding the 50 cent copayment. Given the small momentary value of the prescription fee, these results are of interest to policymakers internationally who wish to reduce copayments rather than abolish them.MethodsA qualitative research design was used; semi structured interviews were carried out. Twenty four GMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The majority of the outcomes analyzed included demand and utilization of health services [ 5 , 15 , 18 – 24 , 30 , 33 , 37 40 , 43 – 45 , 47 – 51 , 55 , 56 , 58 , 60 , 62 – 65 , 68 71 , 75 , 84 , 86 ] and health services costs and expenditures, optimality and efficiency of strategies [ 5 , 15 , 30 32 , 36 , 37 , 39 , 41 – 44 , 53 , 54 , 57 , 59 , 68 , 70 , 73 76 , 83 , 85 , 87 , 94 ]. Limited studies have addressed other important aspects such as access to low-income people [ 49 , 60 , 68 ], reduction in the consumption of both essential (such as preventive and diagnostic services) and non-essential services [ 24 , 44 , 58 ], and people’s attitudes and acceptance [ 25 , 34 , 52 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the outcomes analyzed included demand and utilization of health services [ 5 , 15 , 18 – 24 , 30 , 33 , 37 40 , 43 – 45 , 47 – 51 , 55 , 56 , 58 , 60 , 62 – 65 , 68 71 , 75 , 84 , 86 ] and health services costs and expenditures, optimality and efficiency of strategies [ 5 , 15 , 30 32 , 36 , 37 , 39 , 41 – 44 , 53 , 54 , 57 , 59 , 68 , 70 , 73 76 , 83 , 85 , 87 , 94 ]. Limited studies have addressed other important aspects such as access to low-income people [ 49 , 60 , 68 ], reduction in the consumption of both essential (such as preventive and diagnostic services) and non-essential services [ 24 , 44 , 58 ], and people’s attitudes and acceptance [ 25 , 34 , 52 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Step 4, the researchers met to discuss and revise their initial categories. The research team concluded that saturation (the point at which no new categories emerge from the data; Francis et al, 2010;Sinnott, Guinane, Whelton, & Byrne, 2013) was reached after reviewing the fifth response; they confirmed this by reviewing the remaining 10 sample responses, where no further categories or subcategories emerged. The researchers came to consensus on the final coding scheme (Step 5).…”
Section: Methods Identification Of Behavioral Elementsmentioning
confidence: 97%
“…Co-payments were introduced as a revenue raising measure. Two Irish studies found both co-payments (€0.50 and €1.50) were associated with larger reductions in adherence to less--essential medicines than essential medicines, with anti-depressant and anxiolytic/hypnotic medicines being the exception [34,35]. In 2013, a number of cost containment measures were introduced.…”
Section: Discussionmentioning
confidence: 99%